Academic women in ICT in Asia / Farah Hazwani Mohamad Zulkafli - Farah Hazwani, Mohamad Zulkafli (2005)
The women's population in the Information Communication and Technology field has been indicated doing sadly low. What will be the core reason of this scenario? What can we do to make a change to this matter? As much research has been done to uncover this matter, the progress of women in the ICT field remains the same or rises just slightly. As an overview to this project, intensive research has been done covering the matter of Academic Women in ICT in Asia highlighting the topics such as Why are there few women in the ICT field?, their Challenges and Opportunities, lastly Women's future in ICT. To enhance the research, an online web survey will be set up to enable successful academic women in ICT in Asia to answer the survey questions on the regarding topic. The answers retrieved will be analyzed, producing a final theory in a graph, chart or text form in real-time to summarize the information retrieved from the survey.